2019
DOI: 10.1021/acsmacrolett.9b00534
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of the Nanoreactor Concept for Efficient Synthesis of Multiblock Copolymers via MacroRAFT-Mediated Emulsion Polymerization

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 75 publications
(101 citation statements)
references
References 40 publications
(67 reference statements)
2
90
0
Order By: Relevance
“…50 More recently, Zetterlund and co-workers employed sulfur RAFT emulsion polymerization to also produce methacrylic multiblock copolymers in a controlled fashion. 51 A critical work in the area was published by Harrisson and co-workers who showed that the statistical nature of CRP may limit the control possible in sequence-controlled multiblocks. In particular, his study concluded that for lower DP multiblocks (<6 units per block), defective chains dominate and thus the purity of the materials is compromised.…”
Section: Sequence-controlled Multiblock Copolymersmentioning
confidence: 99%
“…50 More recently, Zetterlund and co-workers employed sulfur RAFT emulsion polymerization to also produce methacrylic multiblock copolymers in a controlled fashion. 51 A critical work in the area was published by Harrisson and co-workers who showed that the statistical nature of CRP may limit the control possible in sequence-controlled multiblocks. In particular, his study concluded that for lower DP multiblocks (<6 units per block), defective chains dominate and thus the purity of the materials is compromised.…”
Section: Sequence-controlled Multiblock Copolymersmentioning
confidence: 99%
“…We decided to use a so-called 'surfactant-free system' [28][29][30][31][32][33] that in our case comprised an amphiphilic poly(N,N-dimethyl acrylamide)-block-poly(butyl acrylate) (PDMAm-b-PBA, 2; refer to Scheme 2) macroRAFT agent. This non-ionic macroRAFT agent was chosen so as to be unlikely to be electrochemically active under the polymerization conditions (a hypothesis confirmed in the present experiments).…”
Section: Raft Free From Exogenous Initiatorsmentioning
confidence: 99%
“…This batch process without any intermediate purification steps performed in environmentally friendly solvent (water), would be very attractive to the industry. [ 201 ] Later the same authors also showed that this strategy could be used to prepare nanoparticle from commodity monomers (methacrylates, acrylates, and styrene) ( Figure ). High molecular weight (up to 140 000 g mol −1 ) multiblock copolymers were prepared in short time periods (up to 3 h) by exploiting the segregation effect (compartmentalization) within the polymeric nanoparticles.…”
Section: Novel (Co)polymers By Raft and Their Propertiesmentioning
confidence: 99%